Peculiarities of receptors distribution to peanut lectin (pna) in the stomach of rats - Mykhailychenko, V.; Kovpak, O. (My University, 2018)
The aim of the research work is to study the distribution of receptors to peanut lectin in the stomach of rats in the early postnatal period of ontogenesis.The selection of stomachs was carried out on the 1 st, 3 rd, 7 th, 11 th, 14 th, 21 st, 45 th and 90 th days after birth.The material was fixed in 10% solution of neutral formalin.Receptors for peanut lectins (PNA) were identified by the standard method «Lectinotest».
Keywords: тези доповідей